AIDS-Related Lymphoma: Resolution with Antiretroviral Therapy Alone. (July 2014) - Hallit, Rabih Riad; Afridi, Muhammad; Sison, Raymund; Szabela, Maria Elaine Y.; Bajaj, Nikki; Alchaa, Roula; Hallit, Souheil; Awkar, Nelly; Boghossian, Jack; Slim, Jihad
Patients with HIV are at increased risk of malignancy, particularly lymphoma, which is the most common malignancy leading to death. With the advent of highly active antiretroviral therapy (HAART), patients live longer but have a longer duration of antigenic stimulation, increasing the prevalence of AIDS-related lymphoma (ARL) in the population living with HIV. Highly active antiretroviral therapy plays a direct role in preserving the immune system, helping to decrease the incidence of ARL. We present a case of a female patient with HIV (CD4 count of 576 cells/mm 3 ) diagnosed with a stage III-B non-Hodgkin lymphoma in 2009 while off HAART. She was subsequently started on HAART, leading to full resolution of her lymphoma without any chemotherapeutic intervention. She was last seen in the clinic in December 2013 without any evidence of recurrence of her lymphoma. To our knowledge, this is the first case report of a stage III-B non-Hodgkin lymphoma in an HIV-infected patient, which resolved with only HAART.